PENGARUH TOTAL ASSET TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT. NIPPON INDOSARI CORPINDO,TBK PERIODE 2013-2023 - Arif Fadhillah; Sri Mardiana (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Total Asset Turnover and Debt To Equity Ratio on Return On Asset at PT Nippon Indosari Corpindo Tbk. both partially and simultaneously. The research method used is a quantitative method with an associative approach. The sample used is the financial report of PT Nippon Indosari Corpindo Tbk. For 11 (eleven) years which has been made into Time Series data. Data analysis in this study uses the classical assumption test, multiple regression analysis, hypothesis testing, and determination coefficient analysis. The results of this study are multiple linear regression equations of Y = -8.496 + 0.167X1 + 0.030X2 + e. Partially, the Total Asset Turnover variable has a positive and significant effect on Return On Asset with the results of t count> t table or (6.213> 2.306) with a significance level of 0.001 <0.05. While the Debt variable To Equity Ratio has a positive and significant influence on Return On Asset with the results of t count> t table or (3.097> 2.306) with a significance level of 0.015 <0.05. Simultaneously, Total Asset Turnover and Debt To Equity Ratio have a positive and significant influence on Return On Asset with a value of f count> ft table, namely (34.127> 4.459) with a significance level of 0.001 <0.05. The coefficient of determination is 86.9%, the remaining 13.1% is influenced by other variables and factors.